(untitled) (Research, Society and Development, 2020)
This research aims to describe the epidemiological and clinical characteristics of patients with type 2 Diabetes Mellitus. It is characterized as an exploratory study, using a form with epidemiological and clinical questions in 88 patients. After descriptive statistical analysis, 46.6% were aged between 60 and 79 years old, 56.8% female, 62.5% with incomplete elementary education, 77.3% not working, 78.4% with income of 1 salary, 36.4% married, 65.9% with a family history of DM, 39.8% smokers, 40.9% alcohol users and 13.6% practice physical activities. In addition, 55.7% reported self-care, 27.3% are amputated, 13.6% undergo nutritional monitoring, 12.5% with angiologists, 40.9% control capillary blood glucose, 77.3% had weight loss, 76, 1% polyuria, 68.2% polydipsia, 72.7% nocturia, 29.5% generalized itching, 65,9% slow wound healing, 84.1% retinopathy, 14.8% nephropathy, and 75% neuropathy. The main conclusions are that the design of the epidemiological profile contributed to investigate the characteristics of DM2 involvement.